Design, synthesis, and biological evaluation of arylmethylpiperidines as Kv1.5 potassium channel inhibitors - Lingyue Zhao; Qian Yang; Yiqun Tang; Qidong You; Xiaoke Guo (Taylor & Francis Group, 2022)
Kv1.5 potassium channel, encoded by KCNA5, is a promising target for the treatment of atrial fibrillation, one of the common arrhythmia. A new series of arylmethylpiperidines derivatives based on DDO-02001 were synthesised and evaluated for their ability to inhibit Kv1.5 channel. Among them, compound DDO-02005 showed good inhibitory activity (IC50 = 0.72 μM), preferable anti-arrhythmic effects and favoured safety. These results indicate that DDO-02005 can be a promising Kv1.5 inhibitor for further studies.